On the existence of Nash Equilibrium in Bayesian Games - Oriol Carbonell-Nicolau; Richard P. McLean (Rutgers University, Department of Economics, 2015)
We furnish conditions on the primitives of a Bayesian game that guarantee the existence of a Bayes-Nash equilibrium. By allowing for payoff discontinuities in actions, we cover various applications that cannot be handled by extant results.
Keywords: C72; 330; Bayesian game; discontinuous game; infinite game of incomplete information; behavioral strategy; distributional strategy; payoff security